APLIKASI KAHOOT DALAM PROSES EVALUASI PEMBELAJARAN - Elvi, Syoviana (Jurnal Sakinah, 2021)
Education using advanced technology and utilizing the maximum will facilitate the learning process and improve the quality of education services. The learning process becomes fun and not wasteful for learners. The era of revolution 4.0 that covers the whole of life requires educational institutions to adapt to the times and technology. Kahoot application as a learning technology platform combines learning evaluation experiences through interactive games and provides a system for student activities. Kahoot platform innovation can help make evaluation activities engaging, interactive, facilitated, and easy to monitor learning outcomes. Kahoot is a platform jointly developed by the Norwegian University of Science and Technology and Johan Brand and Jamie Brooker as initiators for the Joint project. Kahoot has two website addresses: http://Kahoot.com for teachers and https://Kahoot.it for students. The specialty of this platform is to prioritize the process of evaluating learning through group games, but the game can be played individually and must be connected via the internet. Kahoot has become a game-based learning medium with over 34 million active users, and it is recorded worldwide.